The effectiveness of the EU economic governance framework - Stefan Marian Dumitru (CES Working Papers, 2017)
The purpose of this paper is to evaluate the effectiveness of the European Union's (EU) economic governance framework as a key component and driver of the EU - Economic and Monetary Union (EMU). Considerable measures to strengthen the EMU have been undertaken in recent years. In spite of this, its effectiveness in tackling challenges that might appear especially in times of crisis, is still called into question. The creation or reformation of institutions seems to be the most efficient manner in which the Eurozone can advance policies and mechanisms meant to stimulate economic growth. We have found that the major obstacles to more efficiency are two components: 1. the political dimension of the EU – or better said political interference of MS's to protect their own interests; 2. weak EU leadership and vision – this, together with political interests, dilutes significantly the building of institutions, creation and enforcement of policies. Ultimately the question of improving effectiveness of EU economic governance lies in the EU's ability to build a stronger foundation for its institutions. As a modern political and economic entity, subjugated to the MS's, the EU must maintain a balance between state powers and institutional powers, a legal and democratically accountable system of governance, the enforcement and respect of law, whilst also protecting economic growth and the right for a better future.
Keywords: 330; EU; Economic Governance; Effectiveness; EMU